Komunikasi Visual Pada Bumper Acara Televisi (Analisis Semiotika Peirce pada Acara “Sarah Sechan” Di Net TV) - Rinkapati Swatriani (MediaKom : Jurnal Ilmiah Komunikasi, 2019)
Image formation in a television program not only through the content of the program itself but the show can also be through visual communication design that emerged during the program. One is Opening Break Bumper or better known as the bumper. Bumper is the opening animation that appears before starting a television program with a duration of 5-30 seconds. Bumper can be information to viewers about the type and characteristics as well as imaging or visualizing the concept of identity programs.In this study, the authors will focus on the visualization contained in the bumper in the program talk show "Sarah Sechan" that aired on NET TV. Authors interested in researching the bumper as shown has a unique visualization of the terms of the concepts used. Desaigner who designed the bumper using some kind of color as the background image and display several facial expressions Sarah Sechan (as host) and the use of two types of fonts (letters).To investigate the visual signs contained in the bumper of "Sarah Sechan", researchers used a method of analysis for semiotics Peirce's semiotics. Peirce offers three groups based on the sign of the type of relationship between the reader the meaning of items, the items that showed that icon, index, and symbol.The results showed that the bumper of "Sarah Sechan" may be the identity of the program through a visualization program elements and graphics used to characterize the program "Sarah Sechan" that distinguishes it from other programs. Keywords : bumper, visual identity, semiotic